APPROACHES OF PROBING SIGNAL TYPE DETERMINATION OF MEANS LOCAL PROBING FOR DISTRIBUTED POWER GRIDS TECHNICAL CONDITION DIAGNOSTIC - HONCHARENKO, YURII; PRIADKO, VOLODYMIR; POLESHCHUK, I.; SYNKIVSKYI, VIKTOR; OSTRA, NATALIYA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presents the modes of ice detection on a 110 kV overhead line. Methods of detecting damage during ice of power transmission wires are analyzed. Proposals for improving the approaches to determining the damage caused by ice on the wires of overhead power lines have been developed. The article focuses on the method of location probing, which consists in applying a pulse signal to the line and determining the total time spent on its propagation along the wire in the forward and reverse directions after reflection from the end of the line or from high-frequency barrier. In the locational method of detecting ice, information about the appearance of ice is carried by pulses reflected from any inhomogeneity of the wave resistance of the line on it. All negative factors, including ice, change the wave resistance of a long line, creating inhomogeneities in overhead power lines and increases the travel time of the reflected pulse of a given section of the line in the presence of ice. They can be determined by active probing. The problem is that these inhomogeneities can be small in amplitude and active sounding is unable to detect the reflected signal from the homogeneity as the power of noise and interference can be greater, and most importantly they can be on branched power lines. The paper shows that increasing the duration of the probing pulse with the use of different types of modulation allows to increase the energy of the probing signal, to provide the required spectrum width and, accordingly, the resolution of the device at a distance. The article proposes a method of taking into account the "blind zone", in which it is not possible to determine the reflected signals from the place of heterogeneity of overhead power lines. At the time of emission of the probing signal, the input of the receiver is closed and therefore reflected from the homogeneity of the signals do not arrive at the receiver. In FMICW radar, the measurement process to determine the range is to measure the difference between the current frequency of the emitted signal and the frequency of the reflected signal in the ion probe. It is proposed to introduce an algorithm and a method of ionosonde operation for the development of a device for diagnosing the technical condition of electrical distribution networks.